Tratamiento de la hipertrigliceridemia con bezafibrato y acupuntura - Pontaza González, Juana; Macías Hernández, Juana del Socorro; Ortega Cisneros, María Agneris (Universidad Autónoma Metropolitana, 2007)
Introduction. Hypercholesterolemia has a prevalence of 18.8 %. in the general population. In the adult population between 20 and 67 years the prevalence of hypercholesterolemia and hypertrygliceridemia are 11.2%, and 20%, respectively. There exist diverse forms of treatment of the hypertrygliceridemia as diet, drugs and acupuncture. Pharmacological treatment includes the use of fibrates that diminish with efficiency the concentrations of triglycerides and cholesterol; nevertheless the side effects of these drugs its high cost limits its employment. The acupuncture has been used with favorable results for the treatment of the dyslipidemias. Objective. The aim of this study was to evaluate the efficiency of the acupuncture as coadjutant in the treatment of hypertrygliceridemia primarily based on bezafibrate. Design: This was an experimental, longitudinal, opened and prospective study. Material and method: 40 patients with ages between 30 - 60 years of age both sexes were studied, with hypertrigliceridemia regardless the origin of their dyslipidemia. Their values of triglycerides were between >200 - <l000 mg/dl. The patients were recruited in the university community of our institution and people attending external consultation of the General Hospital "Manuel Gea González". Two groups of 20 patients were constituted. The patients of the group A received bezafibrate 200 mg every 24 h (in the night), for 5 weeks. The patients of the group B were treated with bezafibrate 200 mg every 24 h (in the night), and treatment with acupuncture included (IG-11, PC-6, VC12, E-36, E-40, B-4 and B-6) 2 times per week for 5 weeks. The needles remained inserted during 20 minutes, there were carried out two stimulations, one to the beginning and other one before withdrawing the needle Determinations of triglycerides, cholesterol, glucose, arterial pressure and corporal weight were carried out at the beginning and at 5 weeks of determination. Results: Significant differences were not observed in the clinical and epidemiological parameters of the populations between groups. In the patients treated with bezafibrate were noted significant differences (p <0.05) between initial and final observations in the following parameters: cholesterol, triglycerides and corporal weight. Besides, was observed a constant, but not significant decrease (p = 0.08), of the diastolic arterial pressure. In the patients treated with bezafibrate/acupuncture were observed significant differences (p <0.05) between observations in the following parameters: cholesterol, triglycerides, glucose, arterial diastolic pressure and corporal weight. In addition, was observed a constant, but not significant decrease (p = 0.096), of the systolic arterial pressure. At the end of the period of treatment were observed significant differences (p <0.05) between the groups bezafibrate and bezafibrate/acupuncture in cholesterol (p=0.02) and triglycerides (p=0.003). In the comparative analysis for the values of the differences (basal and VS final)) between both groups of treatment there were significant differences (p <0.05) in the following parameters: triglycerides (p=0.021), and corporal weight (p = 0.041). Conclusion: The results of the present study allows to affirm that the acupuncture has an synergic effect with the bezafibrate and produced additional reductions with statistical significance on plasmatic triglycerides, cholesterol, diastolic arterial pressure and corporal weight of the studied patients.; Introducción. En la población general se encuentra una prevalencia de hipercolesterolemia del 18.8%. En la población adulta entre 20 y 67 años las prevalencias de hipercolesterolemia son del 11.2%, y de hipertrigliceridemia del 20%. Existen diversas formas de tratamiento de la hipertrigliceridemia como dieta, medicamentos y acupuntura. Dentro del tratamiento farmacológico se encuentran los fibratos que disminuyen con eficacia las concentraciones de triglicéridos y colesterol; sin embargo los efectos secundarios de estos medicamentos y su elevado costo limita su empleo. La acupuntura se ha empleado con resultados favorables para el tratamiento de las dislipidemias. Objetivo. El objetivo de este estudio fue evaluar la eficacia de la acupuntura como tratamiento coadyuvante del bezafibrato en la hipertrigliceridemia. Diseño. Se realizó un estudio experimental, longitudinal, abierto y prospectivo Material y método. Se estudiaron 40 pacientes con edades entre 30 y 60 años de edad, de cualquier sexo, con valores de triglicéridos > 200 y < l000 mg/dl, sin importar el origen de su dislipidemia. Los pacientes fueron reclutados en la comunidad universitaria de la UAM Iztapalapa y en la consulta externa del Hospital General ³Manuel Gea González´. Se constituyeron dos grupos de 20 pacientes. Los pacientes del grupo A fueron tratados con bezafibrato 200 mg cada 24 h (por la noche), durante 5 semanas. Los pacientes del grupo B fueron tratados con bezafibrato 200 mg cada 24 h (por la noche), y tratamiento con acupuntura en los siguientes puntos (IG-11, PC-6, VC-12, E-36, E-40, B-4 y B-6) 2 veces por semana durante 5 semanas. Las agujas permanecieron insertadas durante 20 minutos, se llevaron a cabo dos estimulaciones, una al inicio y otra antes de retirar la aguja. Se realizaron determinaciones basal y a las 5 semanas de determinación de triglicéridos, colesterol, glucosa, presión arterial y peso corporal. Resultados. No se observaron diferencias significativas en los parámetros clínicos y epidemiológicos de las poblaciones de ambos grupos. En los pacientes tratados con bezafibrato se observaron diferencias significativas (p < 0.05) entre la observación basal y a 5 semanas en los siguientes parámetros: colesterol, triglicéridos y peso corporal. Y se observó una disminución constante, pero no significativa (p = 0.08), de la presión arterial diastólica. En los pacientes tratados con bezafibrato/acupuntura se observaron diferencias significativas (p < 0.05) entre la observación basal y a 5 semanas en los siguientes parámetros: colesterol, triglicéridos, glucosa, presión arterial diastólica y peso corporal. Y se observó una disminución constante, pero no significativa (p = 0.096), de la presión arterial sistólica. Al final del periodo de tratamiento se observaron diferencias significativas (p < 0.05) entre los grupos bezafibrato y bezafibrato/acupuntura en colesterol (p = 0.02) y triglicéridos (p = 0.003). En el análisis comparativo por los valores de las diferencias (basal versus final) entre ambos grupos de tratamiento se encontraron diferencias significativas (p< 0.05) en los siguientes parámetros: triglicéridos (p = 0.021), peso corporal (p = 0.041). Conclusión. Los resultados del presente estudio permite afirmar que la acupuntura tiene un efecto sinérgico con el bezafibrato y produce reducciones adicionales con significación estadística en la reducción de triglicéridos plasmáticos, colesterol, presión arterial diastólica y peso corporal de los pacientes estudiados.